Bazi Bushen Capsule Alleviates Post-Menopausal Atherosclerosis via GPER1-Dependent Anti-Inflammatory and Anti-Apoptotic Effects - Huang, Dan; Wang, Xindong; Zhu, Yunhong; Gong, Juexiao; Liang, Junqing; Song, Yanfei; Zhang, Yiyan; Liu, Linsheng; Wei, Cong (Frontiers in Pharmacology, 2021)
Bazi Bushen capsule (BZBS), as a Chinese medicine used to relieve fatigue, has been proven effective for the treatment of atherogenesis through antilipid effects. To investigate the potential mechanism of BZBS in the anti-atherosclerotic effect, Ovx/ApoE-/- mice were applied to investigate the anti-atherosclerotic efficiency and potential mechanism of BZBS. Therapeutic effect was evaluated based on the number of CD68+ and CD3+ cells, the level of intercellular adhesion molecule-1 (ICAM-1) and vascular cell adhesion molecule-1 (VCAM-1), and the ratio of cleaved caspase-3/caspase-3, as well as increasing ratio of Bcl2/Bax. Human umbilical vein endothelial cells (HUVECs) were chosen to evaluate the role of GPER1. Treatment with BZBS reduced lipid deposition by reducing the numbers of CD68+ and CD3+ cells, the level of ICAM-1 and VCAM-1, and the ratio of cleaved caspase-3/caspase-3, and increasing the ratio of Bcl2/Bax as compared with the control group. In si-GPER1-treated HUVECs, the anti-apoptotic effect of BZBS was decreased. This study revealed that BZBS exhibited a clear effect against atherogenesis via GPER1-dependent anti-inflammatory and anti-apoptotic mechanisms. We believe that this manuscript is informative and useful for researchers pursuing the related alleviation of post-menopausal AS via anti-inflammatory and anti-apoptotic mechanisms.